Sexual Dysfunctional Beliefs Questionnaire (SDBQ): Translation and Psychometric Properties of the Iranian Version. (1st August 2015) - Abdolmanafi, Atefe; Azadfallah, Parviz; Fata, Ladan; Roosta, Mohsen; Peixoto, Maria Manuela; Nobre, Pedro
ABSTRACT: Introduction: The sexual dysfunctional beliefs questionnaire (SDBQ) is a validated measure for assessing dysfunctional sexual beliefs. Aims: The aim of this study was to translate and validate the SDBQ to Iranian context. Methods: In order to translate the questionnaire from English into Persian, a forward–backward procedure was applied. After linguistic validation, the psychometric properties of the Iranian version were assessed for both men and women. A total of 387 participants (226 women and 161 men) completed the SDBQ. Main Outcome Measures: A principle component analysis with varimax rotation was performed for both the male and female samples. Reliability was evaluated by calculating Cronbach's alpha (internal consistency) and test–retest coefficients (intraclass correlation coefficient). Results: The results from the principle component analysis identified six factors in the female version: sexual conservatism and female sexual passivity, beliefs about masturbation, body image beliefs, sexual desire and pleasure as a sin, age‐related beliefs, and denying affection primacy. In the male version six factors were also identified: sex as an abuse of men's power, beliefs related to women's satisfaction, sexual conservatism, female sexual power, "macho" beliefs, and restrictive attitudes toward sex. Findings support the original six‐factor solution for the male sample. For the female sample, although a six‐factor solution was found, original motherhood‐related beliefs were included in the sexual conservatism and female sexual passivity factor, and a new dimension has emerged, related to masturbation beliefs. Additionally, results indicated that the SDBQ had good internal consistency and test–retest reliability in both male and female versions. Conclusion: Current findings support the reliability and validity of the SDBQ in an Iranian sample and suggest its applicability to assess sexual beliefs in both clinical samples and the general population in Iran.